2019
DOI: 10.1021/acs.jpcc.9b04736
|View full text |Cite
|
Sign up to set email alerts
|

Phase, Structure, and Dynamics of the Hydration Layer Probed by Atomic Force Microscopy

Abstract: Using the molecular dynamics method we simulate the hydration layer probed by an atomic force microscope (AFM) tip. We investigate how the AFM tip affects the phase, structure, and dynamics of the intrinsic hydration layer formed on a hydrophobic carbon plate. Without the AFM tip the molecular packing and orientation of the hydration layer are ordered up to the second molecular layer. With approaching the tip, the hydration layer is perturbed and eventually evaporates. The force−distance curve in AFM lacks an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…As H of the domed pillars increased from 12.5 to 16.1 Å, however, ρ decreased because the confinement of water by the solid surfaces was less effective as the bulk water on top of the pillars significantly contributed in this case. Similarly, the prior work reported that layering of water molecules near a solid surface vanished at distances >1 nm from the surface …”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…As H of the domed pillars increased from 12.5 to 16.1 Å, however, ρ decreased because the confinement of water by the solid surfaces was less effective as the bulk water on top of the pillars significantly contributed in this case. Similarly, the prior work reported that layering of water molecules near a solid surface vanished at distances >1 nm from the surface …”
Section: Resultssupporting
confidence: 58%
“…Similarly, the prior work reported that layering of water molecules near a solid surface vanished at distances >1 nm from the surface. 57 We examined how the l−v interface penetrated down into the interpillar gap in the transition from the CB (Φ = 0) to the WZ (Φ = 1) state. Figure 3a,b illustrates the density profiles for various Φs for the surfaces patterned with the domed and rectangular pillars of H = 1.97 nm, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The orientations of OH bonds were checked by varying the tip−surface distance D (Figure 9, left). 31 When the tip was 8 Å above the surface (Figure 9, left), three distinct orientations, called the bulk (b), tangential (t), and dangling (d) orientations, were found in the first molecular layer (at θ ≈ 20°, 100°, and 154°in Figure 9). In the b orientation (Figure 9, right), an OH group is pointing away from the surface and toward the bulk water.…”
Section: Molecular Orientation From Vsfg and Simulationmentioning
confidence: 99%
“…Therefore, a classical MD simulation employing a rigid body model of water with point charges is commonly used. 31 Nevertheless, such a classical MD simulation can be computationally demanding because the tip, surface, and liquid water need to be considered altogether. Simulating a VSFG experiment requires the consideration of the intramolecular vibrations that are quantum mechanical in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation